Editorial: बुद्ध मार्ग दाता हैं, मुक्ति दाता नहीं ! (Bodhi Path, 2024)
In Dhammapada, 276, Buddha says that you must exert effort yourselves; the Tathāgata merely points out the path. By treading this path, you can be completely liberated from the sorrows (Mara) of bondage.The aforementioned statement by the Perfectly Enlightened One is highly relevant for today's era and can contribute significantly to the welfare of the global community. By practically adopting this great teaching from the Dhammapada, humanity can benefit immensely in both material and spiritual  aspects of life. Currently, the global populace, particularly the youth, is grappling with various problems such as unemployment, redundancy, economic disarray, unfulfilled desires, famine, murder, theft, illegal trade, violence, adultery, etc. In pursuit of success, people often resort to unethical and wrong methods, believe in inaction, fate, depend on blessings or grace from gods, gurus, or spiritual teachers, perform and participate in external rituals, and conduct sacrifices, prayers, and worship without trusting in their actions. This results in negative and distressing outcomes.
Keywords: Tathāgata